Simile as a means of shaping the concept of narcissism in Dr. Ravani’s IT’S NOT YOU - Kim Yuliya Sergeyevna (Goodwood Publishing, 2025)
Purpose: This study examines how simile functions as a central stylistic and cognitive device in shaping the concept of narcissism in Dr. Ravani’s It’s Not You, particularly in representing narcissistic abuse, emotional trauma, and recovery. Research Methodology: The research employs a qualitative interpretive literary–stylistic approach. The primary corpus is Dr. Ravani’s It’s Not You, analyzed through simile identification, thematic classification, and theoretical interpretation using Cognitive Metaphor Theory, Narrative Identity Theory, and psychological trauma literature. Results: The findings reveal that similes effectively translate abstract psychological phenomena into vivid experiential images. Similes depict the invisible mechanics of manipulation, the cyclical structure of narcissistic abuse, the emotional validation of victims, the fragile vulnerability behind narcissistic grandiosity, and the complexity of post-traumatic recovery. These figurative expressions enhance reader understanding, emotional resonance, and psychoeducational accessibility. Conclusion: Simile operates not merely as a stylistic ornament but as a powerful cognitive, therapeutic, and narrative tool. Through simile, It’s Not You successfully bridges clinical explanation and emotional experience, fostering both intellectual insight and psychological validation for survivors of narcissistic abuse. Limitation: This study focuses on a single self-help text and relies on interpretive analysis, limiting generalization across broader literary and clinical discourse. Contribution: This research contributes to interdisciplinary studies by integrating cognitive linguistics, literary stylistics, and trauma psychology, highlighting the crucial role of figurative language in psychoeducational and therapeutic narratives.